2021
DOI: 10.1155/2021/8215454
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology Approach for Predicting Targets of Zishen Yutai Pills on Premature Ovarian Insufficiency

Abstract: Background and Purpose. Premature ovarian insufficiency (POI) is a serious reproductive disease in females that is characterized by menstrual and ovulation disorders and infertility. The clinical efficacy of complementary and alternative medicine (CAM) has been reported in POI, including compound Chinese medicine. Zishen Yutai Pills (ZSYTP), a well-known patented Chinese medicine, has been widely used for treating POI; however, the pharmacological mechanism and molecular targets of ZSYTP remain unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…6 A. According to previous studies, the binding strength of a protein is negatively related to its energy; < −1.2 kcal/mol and < −5.0 kcal/mol can be accredited as practical and dynamite docking, respectively [ 36 ]. In terms of potential targets, HRAS and TP53 possessed the best binding outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A. According to previous studies, the binding strength of a protein is negatively related to its energy; < −1.2 kcal/mol and < −5.0 kcal/mol can be accredited as practical and dynamite docking, respectively [ 36 ]. In terms of potential targets, HRAS and TP53 possessed the best binding outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we predicted potential targets of ZSYTP against POI using a network pharmacology approach. Although previous studies have performed network pharmacology analysis and concluded that ZSYTP could be ameliorating POI via glucose metabolism and the HIF-1 signaling pathway, these results were not supported by sufficient experimental validation [ 36 ]. In addition, the use of different pharmacological network analysis methods and databases would inevitably lead to different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The binding energy was used to score the binding affinity of ligand and receptor. It is generally acknowledged that binding energy<0 kcal/mol indicates the interaction of ligand and receptor is spontaneous, and binding energy < -5 kcal/mol means that the ligand and receptor may assemble ( Feng et al, 2021 ; Ni et al, 2021 ; Li et al, 2022a ; Li et al, 2022b ). The docking scores of CUR or the co-crystallized ligand with the selected protein targets (receptors) were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our team conducted a network pharmacology study on the effect of ZSYTP on POI. One hypothesis put forward by our previous study was that ZSYTP upregulates the hypoxia-inducible factor-1 (HIF1) signaling pathway [ 32 ], thereby encouraging oocyte competence through a multitude of pathways. Similarly, the KEGG analysis of ZSYTP on PCOS highlighted the HIF-1 pathway, indicating a possible relationship between the treatment efficacy of ZSYTP and this pathway.…”
Section: Discussionmentioning
confidence: 99%